Aerodynamics of a tall building equipped with a solid screen close to the façade. Issue 225 (June 2022) - Giachetti, Andrea; Bartoli, Gianni; Mannini, Claudio
Abstract: Given the importance recently assumed by permeable building envelopes in modern building architecture, this work addresses the aerodynamic effects of a screen placed close to the front face of a prismatic tall building with a square base. The screen is non-porous and covers the entire building face, but it is open on the lateral sides so to create a thin cavity in connection with the external wind flow. Pressure measurements are carried out in the wind tunnel reproducing a scaled suburban turbulent wind profile. A wind perpendicular to the screened face is assumed as baseline case study, but different azimuthal angles of the wind direction are also considered. Two distances of the screen are tested, namely 1/20 and 1/40 of the building base side length. The experiments reveal a significant aerodynamic influence of the screen, similar to the one observed in previous two-dimensional studies, though less pronounced. For a wind perpendicular to the screen, the major effects of the screen on the building aerodynamics are the decrease of the mean pressure in the upstream part of the side faces, a faster recover of it moving towards the back corners, and a marked increase of the slope of the lateral force coefficient, even implying positive quasi-steady aerodynamic damping in case of cross-flow vibrations. For inclined wind directions, the flow in the cavity has a significant influence on the pressure distribution over the building, generally reducing the pressure coefficients in the region where the flow is ejected. Highlights: Wind tunnel pressure measurements on regular tall building shielded with a solid screen. The presence of the screen influences pressure distributions on the lateral sides. Two- and three-dimensional studies in ABL exhibit common features. For a wind perpendicular to the screen an internal oscillating flow probably occurs.